The hip-spine connection - Nasser, Rima (2015)
The hip and lumbar spine are closely related and can create similar patterns of pain and dysfunction. Diagnosis and treatment of hip and spine–related conditions can be challenging due to symptom overlap. Successful evaluation and treatment of hip and lumbar spine conditions requires a thorough understanding the hip-spine connection. Historically the hip-spine connection has been considered in the context of arthrosis; however, the hip-spine connection also needs to be considered in a younger athletic population. The purpose of this review is to describe the hip-spine connection, discuss the clinical implications of this connection, and offer an approach to diagnosis and treatment. [Orthopedics. 2015; 38(1):49–55.] The authors are from the Department of Orthopedic Surgery (JMR), Mayo Clinic Florida, Jack-sonville, Florida; NOVA Orthopedic & Spine Care (AG), Woodbridge, Virginia; and the American Hip Institute (RN, BGD), Hinsdale Orthopedics, Loyola University Stritch School of Medicine, Westmont, Illinois. The material presented in any Keck School of Medicine of USC continuing education activity does not necessarily reflect the views and opinions of Orthopedics or Keck School of Medicine of USC. Neither Orthopedics nor Keck School of Medicine of USC nor the authors endorse or recommend any techniques, commercial products, or manufacturers. The authors may discuss the use of materials and/or products that have not yet been approved by the US Food and Drug Administration. All readers and continuing education participants should verify all information before treating patients or using any product.